Muco-cutaneous manifestations of chronic kidney disease with or without hemodialysis - Hans, Titiksha; Kumar, Devendra; Agarwal, Soumya; Zaidi, Aliza Shoeb; Mohanty, Swosti; Wadhwa, Aditi (International Journal of Research in Dermatology, 2020)
Background: Mucocutaneous manifestations significantly impair the quality of life of patients with chronic kidney disease (CKD) but are usually understudied. Our objective was to study the patterns and prevalence of mucocutaneous and nail involvement in CKD patients and to compare those in patients with or without haemodialysis. Methods: Ninety patients aged 18-80 years having CKD (M: F=1.64:1) since mean duration of 4.43±9.9 months were studied in an observational cross-sectional study. Sixty-two (68.9%) patients were on hemodialysis since 42.64±63.14 months. Detailed history and examination, and relevant investigations like KOH mount, skin biopsy, gram stain and culture were done when required. Data was analyzed using SPSS version 21 software. Relevant tests were applied, p<0.05 was considered statistically significant. Results: Xerosis in 43 (47.7%), pruritus in 26 (28.9%), ichthyosis in 11 (12.2%), and skin pallor in 7 (7.8%) patients were major dermatoses. Xerosis was more commonly found in patients on haemodialysis (37.8%) as compared to those without dialysis (9.9%) (p-0.046). Bullous lesions, perforating folliculitis and foot ulcers occurred in 1 (1.1%) patient each. Common nail abnormalities were longitudinal ridging (21.1%), leukonychia (13.3%), Lindsay’s half‐and‐half nails (4.4%) and dystrophic nails (4.4%). Mucosal manifestations were coated tongue (2.2%%), angular cheilitis (2.2%), and pigmented tongue (1.1%). Conclusions: Xerosis, pruritus, ichthyosis skin pallor, longitudinal ridging, leukonychia, coated tongue, and angular cheilitis were the common mucocutaneous manifestations in our study. Early recognition and management of these dermatoses plays a crucial role in a holistic patient treatment, reduce disease morbidity and improve their quality of lives.